Paid to perform? Compensation profiles under pure wage and performance related pay arrangements - John G. Sessions; John D. Skåtun (Institute for the Study of Labor (IZA), 2011)
Whilst existing efficiency wage literature assumes detection probabilities of shirkers are exogenous, this paper finds them positively and endogenously dependent on non-shirkers' effort. It shares the result with the endogenous monitoring models where, in some regions, workers reduce effort in response to higher wages, but differs in that firms never operate in those regions. The paper further provides theoretical reasons for the empirical regularity that increased usage of performance related pay (PRP) flattens the pay-tenure profile. Wages and effort increase over the lifecycle, both with and without PRP, but with late payments in PRP falling short of pure wage arrangements.
urn:nbn:de:101:1-201104114042
Keywords: J33; J41; J54; 330; monitoring; tenure; efficiency wages; Leistungsentgelt; Effizienzlohn; Arbeitsleistung; Betriebszugehörigkeit; Leistungsbeurteilung; Theorie